Effectiveness of Animated Video Media for Learning on Early Numeracy Skills of 5–6-Year-Old Children - Sari, Chintiya Febriyana; Iriyanto, Tomas; Astuti, Wuri (Universitas Pendidikan Indonesia Kampus Serang, 2024)
Basic talents such as early numeracy skills require early stimulation. Both in everyday life and when pursuing further education, these skills are invaluable. The use of interesting media is one way to help children develop their numeracy skills from an early age. The purpose of this study was to determine the effect of learning animation video media on children's numeracy skills. This study employed the Intac-Group Comparison design, a type of pre-experimental research. Thirty samples were selected based on the purposive sampling technique; half of them went to the experimental group and half to the control group. A statistical t-test was used to conduct this study. The findings revealed a statistically significant difference between the two groups in terms of the amount of improvement in post-test scores. It can be concluded that animated learning video media positively affected children's early numeracy skills because the significance value of 0.005 0.05 in hypothesis testing exhibited a significant difference between the post-test results of the experimental group and the control group. These results show that animated video media significantly affects the numeracy skills of children aged 5-6 years. This study also recommends continuing to use similar media in improving children's basic early skills.